EVALUASI EFEKTIVITAS PEMBELAJARAN GEOGRAFI DENGAN STRATEGI DISCOVERY- INQUIRY BERBANTUAN ALAT PRAKTIKUM PADA MATERI POKOK ATMOSFER DI SMA NEGERI 16 SEMARANG TAHUN PELAJARAN 2009/2010 - Ferani Mulianingsih (Universitas Negeri Semarang, 2014)
In general, this study aims to obtained objective information about the highschool student learning outcomes through learning by discovery-inquiry strategyand expository. The results showed that, the value of the subject matter ofatmospheric post-test experimental group 1 with data analysis using statisticaltest is obtained tcount value (8,186) with a significance level of 5% was obtainedttable (1.70). Value of the subject matter atmospheric post test experimentalgroup 2 with data analysis using statistical test is obtained tcount value (7.981)with a significance level of 5% was obtained ttable (1.70). Because tcount ttablethen stated that there are differences in learning outcomes between discoveryinquirystrategy which helped with laboratory tools with expository learning, andstated that student learning outcomes in experimental group was better (withclass mean value of 77.49) than the student learning outcomes in control group(with class mean value of 69.03).